The hexameric structure of the human mitochondrial replicative helicase Twinkle. Issue 8 (30th March 2015) - Fernández-Millán, Pablo; Lázaro, Melisa; Cansız-Arda, Şirin; Gerhold, Joachim M.; Rajala, Nina; Schmitz, Claus-A.; Silva-Espiña, Cristina; Gil, David; Bernadó, Pau; Valle, Mikel; Spelbrink, Johannes N.; Solà, Maria
Abstract : The mitochondrial replicative helicase Twinkle is involved in strand separation at the replication fork of mitochondrial DNA (mtDNA). Twinkle malfunction is associated with rare diseases that include late onset mitochondrial myopathies, neuromuscular disorders and fatal infantile mtDNA depletion syndrome. We examined its 3D structure by electron microscopy (EM) and small angle X-ray scattering (SAXS) and built the corresponding atomic models, which gave insight into the first molecular architecture of a full-length SF4 helicase that includes an N-terminal zinc-binding domain (ZBD), an intermediate RNA polymerase domain (RPD) and a RecA-like hexamerization C-terminal domain (CTD). The EM model of Twinkle reveals a hexameric two-layered ring comprising the ZBDs and RPDs in one layer and the CTDs in another. In the hexamer, contacts in trans with adjacent subunits occur between ZBDs and RPDs, and between RPDs and CTDs. The ZBDs show important structural heterogeneity. In solution, the scattering data are compatible with a mixture of extended hexa- and heptameric models in variable conformations. Overall, our structural data show a complex network of dynamic interactions that reconciles with the structural flexibility required for helicase activity.